Mortality rate during exacerbation episodes of Chronic Obstructive Pulmonary Disease (COPD) in elderly individuals hospitalized at a university institution in the State of Paraná, Brazil (Research, Society and Development, 2024)
Acute exacerbations (AECOPD) of COPD negatively impact health status, hospitalization rates, disease progression and health system costs, and other acute events can mimic or worsen AECOPD, which can lead to diagnostic difficulties, especially in elderly patients with multiple associated comorbidities. Advanced age is an isolated risk factor and corresponds to the median age of patients with more severe stages of the disease, therefore, early identification of patients at risk of hospital mortality is crucial. Observational, retrospective, quantitative study, approved by CEP/CAAE 63850022.8.0000.0107. Data were collected from electronic medical records between March/2019 and February/2023, from patients aged ≥60 years with ICD-10 J44 and an active search for medical records of patients with a diagnostic hypothesis of AECOPD with other ICD classifications. They admitted 169 patients with a diagnostic hypothesis of AECOPD in medical evolution, many with other ICD-10 (among them J96, J15, J18, B342, R060) that may be related to AECOPD. Mortality (n=169) was 46.15%. In total, 59 patients with ICD-10 J44 characterized the sample, with a mortality rate of 37.5%. The mortality of patients with AECOPD ˃60 years of age is high, with high urea, LA and CRP on admission being predisposing factors. The present study aimed to analyze clinical factors related to mortality in elderly patients aged 60 or over, hospitalized in an educational institution linked to the Unified Health System (SUS) due to Acute Exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD), and evaluated the existence of possible cases of underdiagnosis among patients.